Constraints on singlet right-handed neutrinos coming from the Z0 width - Escobar, C. O.; Peres, O. L G [UNESP]; Pleitez, V. [UNESP]; Funchal, R. Zukanovich (American Physical Society (APS), 1993)
We study the constraints on masses and mixing angles imposed by the measured Z0 invisible width, in a model in which a singlet right-handed neutrino mixes with all the standard model neutrinos. © 1993 The American Physical Society.